2015
DOI: 10.1111/1467-954x.12268
|View full text |Cite
|
Sign up to set email alerts
|

Support for Far Right Ideology and Anti-Migrant Attitudes among Youth in Europe: A Comparative Analysis

Abstract: The last decade has seen a notable increase in support for far right parties and an alarming rise of right-wing extremism across Europe. Drawing on a new comparative youth survey in 14 European countries, this article provides deeper insight into young people's support for nationalist and far right ideology: negative attitudes towards minorities, xenophobia, welfare chauvinism and exclusionism in relation to migrants. We first map the support for far right ideology among youth in Europe, and then use multileve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 39 publications
1
31
0
1
Order By: Relevance
“…Nationalists tend to perceived outsiders (e.g., immigrants) as threatening; hence, they are more likely to oppose immigrants to acquire national citizenship (Raijman, Davidov, Schmidt, & Hochman, ). Prior research has shown that nationalism is associated with xenophobia, welfare chauvinism, exclusionism, and general anti‐immigration attitudes (Mieriņa & Koroļeva, ). Indeed, nationalists movements, such as Pegida in Germany or Britain First in Great Britain, have publicly expressed their opposition toward immigration, in their point of view the presence of immigrants, especially Muslim immigrants are imminent threat for the nation (Dostal, ; see also “Britain First,” ).…”
Section: Nationalismmentioning
confidence: 99%
“…Nationalists tend to perceived outsiders (e.g., immigrants) as threatening; hence, they are more likely to oppose immigrants to acquire national citizenship (Raijman, Davidov, Schmidt, & Hochman, ). Prior research has shown that nationalism is associated with xenophobia, welfare chauvinism, exclusionism, and general anti‐immigration attitudes (Mieriņa & Koroļeva, ). Indeed, nationalists movements, such as Pegida in Germany or Britain First in Great Britain, have publicly expressed their opposition toward immigration, in their point of view the presence of immigrants, especially Muslim immigrants are imminent threat for the nation (Dostal, ; see also “Britain First,” ).…”
Section: Nationalismmentioning
confidence: 99%
“…While much information can be found on any religious inspired attack, there is very little information given on, for instance, the attack on a mosque in Enschede in the Netherlands in 2016. The picture of extremism is further enhanced by a historical peak in support of extreme right parties in the national governments embedded in discriminatory European societies (André and Dronkers, 2016), such as the Front Nationale in France or the Party for Freedom in the Netherlands and the Alternative für Deutschland in Germany (Fekete, 2009;Mieriņa and Koroļeva, 2015). Also, leftwing and anarchist extremism as well as nationalist and separatist extremism is on the rise, though to less of an extent; so too are young people being increasingly recruited into violent radicalization (RAN, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Media commentators have stressed factors such as economic distress, immigration and fears of cultural and identity dilution (Aisch, Pearce & Rousseau, 2017;Der Spiegel, 2010;Lebor, 2016;New York Times, 2016). Academic arguments point to these and other factors (Carter, 2005;Cochrane & Nevitte, 2014;Lubbers & Coenders, 2017;Mieriņa & Koroļeva, 2015;Stockemer, 2017). For example, Golder (2016) offers a useful categorization of those arguments, in line with previous research (see Halikiopoulou, Mock, & Vasilopoulou, 2013;Kitschelt, 1995;Norris, 2005;Van der Brug, Fennema, & Tillie, 2005).…”
Section: Introductionmentioning
confidence: 79%